TINGKAT PENGETAHUAN PENGGUNAAN ANTIBIOTIK JENIS AMOXICILLIN PADA MASYARAKAT DESA PILANGGEDE KECAMATAN BALEN KABUPATEN BOJONEGORO - Ainu Zuhriyah; Nawafilla Februyani; Laily Alifatul Jamilah (Jurnal Ilmiah Hospitality, 2020)
Antibiotics as a cure for infectious diseases must be used correctly and effectively. One of the antibiotics that are often used in the community is amoxicillin. If amoxicillin is consumed not according to the rules of use, the risk of resistance will increase. The purpose of this study is to know the level of public knowledge in the use of antibiotics, especially amoxicillin. There are 50.7% of the people who have sufficient knowledge in Vilaggers Pilanggede, Balen Sub-District, Bojonegoro Regency. The research use descriptive qualitative research and sampling use Non Random Sampling technique that is Purposive Sampling involving 65 respondents. The variables studied were public knowledge about the use of antibiotics, especially amoxicillin. The results obtained are community knowledge about antibiotics, especially amoxicillin, which is classified as sufficient knowledge, which is 33 (50.7%).